Glutathione in Health and Disease - Erkekoglu, Pinar; Kocer-Gumusel, Belma (IntechOpen, 2018)
Reduced glutathione (GSH) is the most important thiol in living organisms. It is the key component of antioxidant system and serves as a free radical scavenger. There is a cycle of GSH in biological systems and this cycle provides higher intracellular levels of GSH. GSH depletion and apparent oxidative stress may cause toxicity and can affect the general well-being of the organism. GSH was shown to be preventive against aging, cancer, heart disease, infections and dementia. This book is mainly focused on GSH in health and disease. The readers will gain qualified scientific knowledge on the diverse functions of GSH, the importance of GSH status against oxidative stress and the interaction between GSH and nervous system-related infections from this book.